ANALYSIS OF STATE SUPPORT EFFECTIVENESS FOR HIGH-TECH INDUSTRIES - I. V. Milkina; S. V. Lits (Вестник университета)
The issue of the effectiveness of state support for sectors of the domestic economy, engaged in the development and production of products using high technologies, has been considered. Вased on the analysis of indicators characterizing the effectiveness of state support measures in this area, the conclusion has been made about the lack of effectiveness of this activity. It also has been concluded, that measures to support the domestic economy sectors related to its high-tech segment by the state are insufficient, which leads to backwardness of Russia behind the leading economically developed countries (the USA, Japan, Germany) in the development of high-tech industries of the civil sphere. This situation requires the adoption of measures to support and develop the high-tech segment of the domestic economy at the state level. The condition for increasing the effectiveness of measures of state support for the high-tech complex is to increase allocations for R&D in those industries whose products are able to compete with or surpass similar foreign models on an equal basis.